Digital Business Communication Strategy Barometer: Stimulation of K-Pop Brand Ambassadors for Consumers of E-commerce Products in Indonesia - Agung, Halim; Farady Marta, Rustono; Stefanus Kembau, Agung; Firellsya, Gabriela; Venness, Venness; Brigitta Indrawan, Genoveva; Christanti, Christanti (Green Publisher, 2023)
The popularity of K-Pop is considered to be in line with the adoption of certain product brands, now this is increasingly happening in Indonesia. Especially for companies that run digital business communication strategies through e-commerce channels, so they need to be stimulated through their brand ambassadors. This research is intended to make a barometer of digital business communication strategies through measuring the impact of K-Pop Brand Ambassador stimulation on purchasing decisions of e-commerce consumers in Indonesia. The data is calculated using the PLS-SEM analysis method with the calculation tools used are SmartPLS and G*Power. This research is based on simple random sampling involving 133 respondents. The test results show that the impact of K-Pop brand ambassadors on consumer purchasing decisions for e-commerce products in Indonesia is only 0.662, so it does not have a significant effect. Companies that use digital business communication strategies need to involve other, more substantial components, especially in increasing their brand interactions with consumers.